Gender Identity and Relative Income within Households: Evidence from Sweden - Karin Hederos Eriksson; Anders Stenberg (Institute for the Study of Labor (IZA), 2015)
Bertrand et al. (2015) show that among married couples in the US, the distribution of the share of the household income earned by the wife exhibits a sharp drop just to the right of .50. They argue that this drop is consistent with a social norm prescribing that a man should earn more than his wife. We repeat this analysis for Sweden, ranked as one of the world's most gender equal countries. Analyzing Swedish population register data, we do not find support for the norm that a man should earn more than his wife.
Keywords: D10; J12; J16; 330; gender roles; marriage market; gender gap; gender identity